Authentic Marine Research Experiences for Low-Income and First Generation High School Students Used to Level the Playing Field and Decrease Attrition in STEM. Issue 1 (1st November 2021) - Kast, Dieuwertje J.
Summer research experiences are often life-changing for first generation high school students of color, especially in the marine biology field. The University of Southern California (USC) Leslie and Bill McMorrow Neighborhood Academic Initiative (USC NAI ) partners with STEM professionals, laboratory scientists, local marine-based field sites, marine educators, and laboratory managers to facilitate hands-on, inquiry-based research and learning experiences for the high school students that participate in their program. These partnerships collaborate with instructors to deliver an ocean research methods course to the students. The learning goals of the course include providing the foundational scientific skills needed to succeed in the STEM workforce and learning about various marine related careers. As a result of the ocean research methods course and other STEM interventions with USC NAI, 42% of NAI grads who have gone to USC have declared a STEM major as freshmen since 2013.